REVEALING THE IMPORTANCE OF GREEN COLLABORATION IN GREEN INNOVATION: ENTREPRENEURIAL MARKETING PERSPECTIVE - Darmawan, Esther; Radianto, Wirawan Endro Dwi; Kaihatu, Thomas Stefanus; Utami, Christina Whidya (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
Green innovation (GI) is often perceived as unnecessary for companies, while the amount of packaging waste with the potential to pollute the environment continues to increase significantly. Without extraordinary action, this will lead to contamination of ecosystems and a threat to human health. Therefore, this research aimed to explore the role of green collaboration (GC) in enhancing innovation and improving company performance (CP), with a particular emphasis on how the synergy of innovation and collaboration serves as a dimension of entrepreneurial marketing (EM). A quantitative method was used through a survey of 120 division heads and company owners in Indonesia. Moreover, data analysis was conducted using Structural Equation Model (SEM) method with Partial Least Squares (PLS) method. The results showed that both green innovation and green collaboration had a positive impact on company performance. However, green collaboration did not demonstrate a statistically significant moderating effect. This suggests that companies need to consider other strategic alliances to maximize the synergy between green innovation and green collaboration. The results can serve as a guide for companies in designing effective innovation and collaboration strategies to achieve sustainability and competitive advantage. However, a key limitation is that the strategy may not be applicable in another industry.